EVALUATION OF ANTI-DIABETIC ACTIVITY OF METHANOL EXTRACT OF FLACOURTIA JANGOMAS (LOUR) IN STREPTOZOTOCIN INDUCED DIABETIC RATS - N. SURJIT SINGH; M. GEETHA; P. AMUDHA; AVIJIT CHAKRABORTY (International Journal of Pharma and Bio Sciences, 2010)
The present study was undertaken to evaluate the antidiabetic activity of methanol extract of Flacourtia jangomas (lour) in streptozotocin induced diabetic rats. In this study, the acute and subacute anti hyperglycaemic effect of the two different doses (200 and 400 mg/kg b.w.p.o) of plant extracts were investigated. Fasting blood glucose level, body weight and serum lipid profiles were evaluated in normal and diabetic rats. The liver and muscle glycogen level were also evaluated. Supplementation of this extract significantly reduces the fasting blood glucose level and increases the glycogen level as compared to diabetic control. In the extracts treated groups, serum lipid profile shows a significant improvement. For all the estimated parameters, the results of the extract treated groups were restored to the near normal level, thereby indicating good antihyperglycemic activity of the methanol extract of Flacourtia jangomas (lour).